Community-Effectiveness of Temephos for Dengue Vector Control: A Systematic Literature Review - George, Leyanna; Lenhart, Audrey; Toledo, Joao; Lazaro, Adhara; Han, Wai Wai; Velayudhan, Raman; Runge Ranzinger, Silvia; Horstick, Olaf (PLOS Neglected Tropical Diseases, 2015)
Author Summary Dengue remains largely uncontrolled globally. Prevention and control relies on vector control methods, and good case management is key to reducing mortality. For vector control several methods exist, including biological and chemical interventions, and environmental modifications. The application of the organophosphate larvicide temephos to water storage containers is one of the most commonly employed dengue vector control methods. This systematic literature review assesses the community-effectiveness of temephos in controlling both vectors and dengue transmission when delivered either as a single intervention or in combination with other interventions. 27 studies were included in this systematic review (11 single intervention studies and 16 combined intervention studies). All 11 single intervention studies showed consistently that using temephos led to a reduction in entomological indices. Although 11 of the 16 combined intervention studies showed that temephos application together with other chemical vector control methods also reduced entomological indices, this was either not sustained over time or–as in the five remaining studies—failed to reduce the immature stages. Temephos was found to be effective at suppressing entomological indices, however, the same effect has not been observed when temephos was applied in combination with other interventions. There is no evidence to suggest that temephos use is associated with reductions in dengue transmission.